Hypatia: Another Daughter of the Nile (Devenires, 2010)
This article presents a profile of Hypatia of Alexandria, an Egyptian mathematician, astronomer and philosopher who lived during the epoch ofthe decadence of the Roman Empire. It describes Hypatia’s contributions to knowledge and offers an account of the successive adoptions of her figure as a symbol of reason in the face of obscurantism. Indeed, the historical figure was absorbed by the legendary one, and the latter was constructed on the basis of the cruel nature of her murder at the hands of a group of Christians called parabolans. The conflicts that led to Hipatia’s death, though underlaid by the dichotomy of paganism and Christianity, are more complex, etched in a tangle of vested interests between the prefect and the bishop of Alexandria. Ignorance of the work of philosophers and scientists has been a common occurrence throughout history, such that historical reconstructions can only be fragmentary, though clearly necessary to be rescued from ignorance or, as in the case of Hypatia, to illustrate the reasons why she has become a symbol of Greco-Roman rationality in the face of the medieval shadows that loomed in the early 5th century.